Lessons Learned from Rapid Development of CPAP Ventilator Vent-I during Covid-19 Pandemic in Indonesia - Syarif Hidayat; Jam'ah Halid; Tatacipta Dirgantara; Mipi Ananta Kusuma; Hari Utomo; Reza Widianto Sudjud; Ike Sri Rejeki; Sandro Mihradi; Sri Raharno; Dadang Rukanta; Hari Tjahjono (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Here, lessons learned during the development of the CPAP ventilator 'Vent-I', aimed to help COVID-19 patients with breathing difficulties, are presented. Within only weeks, the Vent-I was developed, complying with functionality, safety and reliability requirements and passing the clinical trial. It was then distributed to hospitals all over Indonesia. Two billion rupiahs were raised through crowdfunding within one week. When the project was officially closed, more than one thousand Vent-I devices had been distributed and more than twelve and a half billion rupiahs had been raised. Currently, commercialization and mass production of the device have been started. From this project several lessons can be learned. First and foremost, the spirit of gotong royong